A digital audio data protection method using parametric action of generalised triangle group on GF(28) - Aqsa Zafar Abbasi; Ayesha Rafiq; Badr M. Alshammari (Ain Shams Engineering Journal)
The parametrization of the action of the modular group PSL(2,Z) for the triangle groups is extended for Δ(2,3,k) to the finite generalised triangle groups 〈u,v|u2=v3=wk=1〉 where w=uvuvuv2uvuv2. Also, based on the resulting parametric equations, the authors have presented an audio encryption approach in this study. The extremely secure S-Box, which is then utilised to encrypt audio signals, is built using parametric equations. Utilising several audio sources, the effectiveness of the current approach is assessed. According to the simulation specially differential analysis average NSCR 99.96% and average UACI 33.33% as well as comparison results, the recommended method might prevent cryptographic vulnerabilities and produce reliable encryption results.